2018
DOI: 10.1371/journal.pone.0196630
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya virus infection in Aruba: Diagnosis, clinical features and predictors of post-chikungunya chronic polyarthralgia

Abstract: BackgroundChikungunya virus (CHIKV) emerged in Aruba for the first time in 2014. We studied the clinical presentation of acute CHIKV infection and the contribution of serologic and molecular assays to its diagnosis. In a cohort of confirmed CHIKV cases, we analysed the frequency, duration and predictors of post-chikungunya chronic polyarthralgia (pCHIK-CPA), defined as joint pains lasting longer than 6 weeks or longer than 1 year.MethodologyPatient sera obtained within 10 days of symptom onset were tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
33
4
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 82 publications
(113 reference statements)
6
33
4
9
Order By: Relevance
“…With the exception of joint pain, the symptoms of acute chikungunya typically resolve over a few days to 1 week (1,68). Approximately 50% of patients have chronic arthralgia and/or arthritis at 3 to 6 months, and over 25% of patients may still have symptoms at 12 months, which negatively impacts quality of life during recovery (68,(176)(177)(178)(179)(180). Although significant heterogeneity regarding the rate of chronic joint pain following chikungunya exists in the literature, older age (Ͼ35 to 60 years) and preexisting joint disease have been consistently associated with this outcome (176,177).…”
Section: Prognosis Outcome and Preventionmentioning
confidence: 99%
“…With the exception of joint pain, the symptoms of acute chikungunya typically resolve over a few days to 1 week (1,68). Approximately 50% of patients have chronic arthralgia and/or arthritis at 3 to 6 months, and over 25% of patients may still have symptoms at 12 months, which negatively impacts quality of life during recovery (68,(176)(177)(178)(179)(180). Although significant heterogeneity regarding the rate of chronic joint pain following chikungunya exists in the literature, older age (Ͼ35 to 60 years) and preexisting joint disease have been consistently associated with this outcome (176,177).…”
Section: Prognosis Outcome and Preventionmentioning
confidence: 99%
“…9,16 Features were comparable with other chikungunya cohorts in literature as well. 17 Lymph adenopathy was common in nondiabetic patients in our series, while neurological and cardiovascular complications were less common. But we found acute kidney injury in one-tenth of our cases.…”
Section: Discussionmentioning
confidence: 59%
“…Regarding the laboratory findings, leukopenia showed a strong association with hospital admission due to CHIKV infection. A study carried out on a Caribbean island showed that none of the patients infected with CHIKV were hospitalized and no infection-related mortality was recorded 12 . This confirms that the disease has low lethality providing the patients do not have comorbidities and factors associated with death 11 .…”
mentioning
confidence: 99%
“…This confirms that the disease has low lethality providing the patients do not have comorbidities and factors associated with death 11 . The infection cases are usually referred by family physicians for laboratory confirmation of suspected acute infection, and most cases are treated in primary care facilities 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation